2022
DOI: 10.3389/fonc.2022.946253
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of XIAP promotes lung adenocarcinoma brain metastasis by modulating ceRNA network

Abstract: Dysregulation of XIAP has been shown to affect the progression of a variety of cancers, including lung adenocarcinoma (LUAD). However, the function and mechanisms of XIAP in lung adenocarcinoma with brain metastasis (LUAD-BM) remains poorly understood. In this study, we analyzed the differential mRNA of 58 lung adenocarcinomas samples and 28 lung adenocarcinomas with brain metastases in GEO database. 191 differentially expressed mRNAs were significantly associated with immune response, the proliferation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The treatment method of blocking the inhibitory receptor programmed cell death-1 (PD-1) on the surface of T lymphocytes has significantly improved both the therapy mode and also the prognosis of carcinoma. Moreover, the 5-year survival rate of patients with advanced lung carcinoma has increased to 16% (5). The PACIFIC study suggested that immune maintenance therapy after radical concurrent chemoradiotherapy for stage III inoperable locally advanced NSCLC can significantly improve the survival of patients, and it has become the standard treatment recommended by the guidelines (6).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment method of blocking the inhibitory receptor programmed cell death-1 (PD-1) on the surface of T lymphocytes has significantly improved both the therapy mode and also the prognosis of carcinoma. Moreover, the 5-year survival rate of patients with advanced lung carcinoma has increased to 16% (5). The PACIFIC study suggested that immune maintenance therapy after radical concurrent chemoradiotherapy for stage III inoperable locally advanced NSCLC can significantly improve the survival of patients, and it has become the standard treatment recommended by the guidelines (6).…”
Section: Introductionmentioning
confidence: 99%